2009
DOI: 10.1002/jpln.200700132
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon–stock changes in Flemish grassland soils from 1990 to 2000

Abstract: Total soil organic-carbon (SOC) stocks for grassland soils in Flanders (N Belgium) were determined for the Kyoto Protocol reference year 1990 and 2000 in order to investigate whether these soils have been CO 2 sinks or sources during that period. The stocks were calculated by means of detailed SOC datasets, which were available at the community scale for the whole of Flanders. The total SOC stocks for Flemish grassland soils (1 m depth) were estimated at 38 Mt SOC in 1990 and 34 Mt SOC in 2000. The loss of SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…Somewhat smaller estimates have been reported for cropland (90 t C ha −1 ), grassland (118 t C ha −1 ) and forest soils (98 t C ha −1 ) in southeast Germany (Wiesmeier et al , ), mainly because there is less SOC below the top‐soil (A horizon). Meersmans et al () also found less SOC stored in the 0–100‐layer under cropland and grassland in northern Belgium (86 and 108 t C ha −1 , respectively), while another study of North Belgian soils (Mestdagh et al , ) reported SOC storage ranging from 111 to 163 t C ha −1 in grasslands (excluding grasslands on polders and dunes). For Scottish arable soils, Chapman et al () reported SOC stocks of 111 t C ha −1 .…”
Section: Resultsmentioning
confidence: 93%
“…Somewhat smaller estimates have been reported for cropland (90 t C ha −1 ), grassland (118 t C ha −1 ) and forest soils (98 t C ha −1 ) in southeast Germany (Wiesmeier et al , ), mainly because there is less SOC below the top‐soil (A horizon). Meersmans et al () also found less SOC stored in the 0–100‐layer under cropland and grassland in northern Belgium (86 and 108 t C ha −1 , respectively), while another study of North Belgian soils (Mestdagh et al , ) reported SOC storage ranging from 111 to 163 t C ha −1 in grasslands (excluding grasslands on polders and dunes). For Scottish arable soils, Chapman et al () reported SOC stocks of 111 t C ha −1 .…”
Section: Resultsmentioning
confidence: 93%
“…In the north Belgian grassland soils, Mestdagh et al (2009) estimated a decrease in SOC between 1990. from 38 to 34 Mt) due to a reduction of C input from manure and conversion to temporary grasslands.…”
Section: Discussionmentioning
confidence: 98%
“…3). In several SOC studies in Europe it was also assumed that a decreased application of farmyard manure resulted in a decreased C supply in cropland soils (Capriel, 2013;Goidts and van Wesemael, 2007;Mestdagh et al, 2009;Sleutel et al, 2007).…”
Section: Implications Of Yield Stagnation: Decrease Of Agricultural Smentioning
confidence: 99%